Voices of East Asia : essential readings from antiquity to the present - Childs, Margaret Helen; Hope, Nancy (New York : Routledge, 2015)
'Voices of East Asia provides significant yet accessible readings in translation chosen to stimulate interest in the long and rich cultural history of East Asia, the countries of China, Japan, and Korea. The readings range from ancient to modern, elite to popular, and include poetry, stories, essays, and drama. Each section begins with a broad but brief overview of that country's political and cultural history. Each reading is preceded by a concise explanation of its literary and cultural context. As expertise in East Asian studies has exploded in the West in recent decades, a novice could be overwhelmed by all the materials available now. In this volume, however, the reader will find a manageable set of texts that may be read on their own, as part of a world literature course, or as supplementary readings for an East Asian history class. As economic and political news from East Asia sweeps across the world, this anthology aims to provide a taste of the enduring traditions upon which contemporary East Asia is built, a glimpse into the hopes and fears, love and sorrow in the hearts of the people behind the headlines. This anthology will be welcomed by students and scholars of Asian history, culture, society and literature.'--
Includes bibliographical references : pages 335-338 and index.
Keywords: East Asian literature -- Translations into English; Chinese literature -- Translations into English; Japanese literature -- Translations into English; Korean literature -- Translations into English